Industrial Relations at the Millennium: Beyond Employment? - Giles, Anthony (Labour / Le Travail, 2000)
This essay explores the current state of the field of Industrial Relations. The first part of the essay traces the emergence of IR out of the general concern with the 'labour question" to form a distinct field of study and research in the Angio-American countries. The second part argues that the field has been plagued by a profound crisis of relevance in the 1980s and 1990s, registered by a decline in its importance within universities, a shrinking of its academic associations, a loss of interest on the part of its traditional audience, increased isolation from other disciplines, and a theoretical incapacity to come to grips with the sweeping changes that have occurred in labour markets, the workplace, and the wider political economy. This situation is leading to a redefinition of the field as "Employment Relations." In the third part of the essay, this drift towards Employment Relations is criticized for moving the field more squarely into the area of managerial science, for leaving it incapable of analyzing future waves of collective mobilization, and for its continued adherence to a geographically and historically constricted conceptual foundation. A better strategy, it is suggested, would be to go beyond employment by reconceptualizing the field in terms of "work relations."